Effects of inbound attendees of a mass gathering event on the COVID-19 epidemic using individual-based simulations. - Masaya M Saito; Kotoe Katayama; Akira Naruse; Peiying Ruan; Michio Murakami; Tomoaki Okuda; Tetsuo Ysutaka; Wataru Naito; Masaharu Tsubokura; Seiya Imoto (PLoS ONE)
Given that mass gathering events involve heterogeneous and time-varying contact between residents and visitors, we sought to identify possible measures to prevent the potential acceleration of the outbreak of an emerging infectious disease induced by such events. An individual-based simulator was built based on a description of the reproduction rate among people infected with the infectious disease in a hypothetical city. Three different scenarios were assessed using our simulator, in which controls aimed at reduced contact were assumed to be carried out only in the main event venue or at subsequent additional events, or in which behavior restrictions were carried out among the visitors to the main event. The simulation results indicated that the increase in the number of patients with COVID-19 could possibly be suppressed to a level equivalent to that if the event were not being held so long as the prevalence among visitors was only slightly higher than that among domestic residents and strict requirements were applied to the activities of visitors.